1999
DOI: 10.1038/9219
|View full text |Cite
|
Sign up to set email alerts
|

Role of the posterior parietal cortex in updating reaching movements to a visual target

Abstract: The exact role of posterior parietal cortex (PPC) in visually directed reaching is unknown. We propose that, by building an internal representation of instantaneous hand location, PPC computes a dynamic motor error used by motor centers to correct the ongoing trajectory. With unseen right hands, five subjects pointed to visual targets that either remained stationary or moved during saccadic eye movements. Transcranial magnetic stimulation (TMS) was applied over the left PPC during target presentation. Stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

60
425
10
9

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 728 publications
(504 citation statements)
references
References 32 publications
60
425
10
9
Order By: Relevance
“…A second alternative explanation would suggest that the modulation of the excitability of the CST might be triggered by the output of a conflict monitoring system involving the DLPFC and the ACC (Botvinick et al, 2001). Previous studies administered single or brief burst of high-frequency magnetic pulses to different regions of the brain in specific time intervals respect to an event in order to momentarily disrupt the corresponding neural activity at specific stages of the task (Desmurget et al, 1999;Pascual-Leone et al, 2000;Vesia et al, 2010). Particularly, applying single pulses to these regions at specific time intervals respect to the commission of mistaken responses might help to disentangle i) their functional role by measuring the behavioral effect of the suppression of its activity and (ii)the exact time-course of their activation.…”
Section: Discussionmentioning
confidence: 99%
“…A second alternative explanation would suggest that the modulation of the excitability of the CST might be triggered by the output of a conflict monitoring system involving the DLPFC and the ACC (Botvinick et al, 2001). Previous studies administered single or brief burst of high-frequency magnetic pulses to different regions of the brain in specific time intervals respect to an event in order to momentarily disrupt the corresponding neural activity at specific stages of the task (Desmurget et al, 1999;Pascual-Leone et al, 2000;Vesia et al, 2010). Particularly, applying single pulses to these regions at specific time intervals respect to the commission of mistaken responses might help to disentangle i) their functional role by measuring the behavioral effect of the suppression of its activity and (ii)the exact time-course of their activation.…”
Section: Discussionmentioning
confidence: 99%
“…Desmurget and colleagues have provided a tool to determine behaviorally whether the dorsal stream is critically involved in specific aspects of a task (Desmurget et al, 1999;Pisella et al, 2000). Using transcranial magnetic stimulation and a patient study, they showed that part of the dorsal route (the posterior parietal cortex) is necessary for fast (less than 150-ms latency) corrections of ongoing pointing movements to perturbations of object locations.…”
mentioning
confidence: 99%
“…This indicates that the right PPC is not critically involved in updating self-location along straight paths. We found this surprising, considering the aggregation of evidence for impaired eye and arm position updating after PPC lesions [15,16,29,65]. Before abandoning the notion that the PPC is a critical structure for updating during locomotion, however, other types of locomotion and more complex trajectories should be tested.…”
Section: Discussionmentioning
confidence: 92%
“…Future testing with left hemisphere patients promises to shed light on this issue. Evidence is scant for lateralization of the neural substrates of arm position updating, but there are reports that lesions to or stimulation of the left PPC can lead to de®cits in updating during reaches [15,65], at least for reaches made by the contralateral arm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation